(untitled) (Jurnal Manajemen dan Organisasi, 2016)
Bogor Agricultural University (IPB) is one of popular university in Indonesia, it was concern to the provided of the human resources which have good quality and competent. That’s seven values of corporate culture are academic excellent, spiritualism, persevering, teamwork, empathy, responsible, and commitment. The objectives of this research are: (1) to identification organization culture in IPB, (2) to know the application of organization culture in IPB, (3) to recommend the model of internalization organization culture. This research used by descriptive analysis and Analysis Hierarchy Process (AHP) for analyzing internalization organization’s culture in Bogor Agricultural University. According to the survey, dept interview and literary analysis, the organization culture in IPB is including in power culture, person culture, and achievement culture. The application of organization’s culture in IPB is not maximal practice yet. The barrier of organization culture did not legitimate by Academic Senator, so the program that implementation organization culture is not yet. The factors that support organization culture in IPB is support from institution and human resource in IPB. The factor most influence in organization culture internalization in IPB is leadership. The actor most influence in organization culture internalization in IPB is head of university in IPB. The most influence objectives in organization culture internalization are actualization vision and mission organization. The alternative scenario in organization culture internalization is implementation learning organization in IPB.